Study of the Effect of the Incorporation of tio2 Nanotubes on the Mechanical and Photodegradation Properties of Polyethylenes - Zapata-Ramirez, P; Vasco-Calle, D (Elsevier Ltd, 2017)
TiO2 nanotubes (TiO2-Ntbs) synthesized by a hydrothermal method with a diameter of ca. 5 nm were used as filler to prepare polyethylene (PE) and linear low density polyethylene (LLDPE) composites by melt blending. Nanotubes were used either as synthesized or organically modified with hexadecyltrimethoxysilane (Mod-TiO2-Ntbs). In some cases nanoparticles form secondary structures with sizes around 100 nm and agglomerates larger than 2 μm are also seen by transmission electron microscopy (TEM). In terms of mechanical properties, the addition of TiO2-Ntbs resulted in a composite, LLDPE/TiO2-Ntbs, with improved properties. Compared with the pure polymer, Young s modulus increased by ca. 50%, while yield stress increased by ca. 35%. On the other hand, PE/Mod-TiO2-Ntbs and LLDPE/Mod-TiO2-Ntbs with 5 wt% filler loading showed higher E′ values in the storage modulus at low temperatures than either neat PE and LLDPE. The photodegradation properties of the PE/Mod-TiO2-Ntbs and LLDPE/Mod-TiO2-Ntbs composites were studied. The largest increase of chemiluminescence emission (CL) and carbonyl index (CI) was found for LLDPE/Mod-TiO2-Ntbs during photoaging. That behavior may be due to large branching of the polymer, and to the presence of the nanotubes incorporated into the LLDPE, which promoted and accelerated its photodegradation due to reactive species generated during irradiation. © 2016 Elsevier Ltd